2018
DOI: 10.1002/14651858.cd002922.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive treatment for proliferative lupus nephritis

Abstract: Analysis 1.1. Comparison 1 Mycophenolate mofetil (MMF) versus IV cyclophosphamide (CPA), Outcome 1 Death. Analysis 1.2. Comparison 1 Mycophenolate mofetil (MMF) versus IV cyclophosphamide (CPA), Outcome 2 Remission. Analysis 1.3. Comparison 1 Mycophenolate mofetil (MMF) versus IV cyclophosphamide (CPA), Outcome 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(109 citation statements)
references
References 193 publications
5
93
0
1
Order By: Relevance
“…In class III-IV LN, an updated Cochrane systematic review suggested similar efficacy of mycophenolate mofetil/mycophenolate acid (MMF/MPA) compared with cyclophosphamide (CY), 33 with possible ethnic/racial differences, that is, MMF potentially being more efficacious in African-Americans. 34 The 10-year Euro-Lupus Nephritis Trial data showed equal efficacy of low-dose versus high-dose CY, 24 and the low-dose regimen has been used in non-European populations.…”
Section: Initial Treatmentmentioning
confidence: 99%
“…In class III-IV LN, an updated Cochrane systematic review suggested similar efficacy of mycophenolate mofetil/mycophenolate acid (MMF/MPA) compared with cyclophosphamide (CY), 33 with possible ethnic/racial differences, that is, MMF potentially being more efficacious in African-Americans. 34 The 10-year Euro-Lupus Nephritis Trial data showed equal efficacy of low-dose versus high-dose CY, 24 and the low-dose regimen has been used in non-European populations.…”
Section: Initial Treatmentmentioning
confidence: 99%
“…However, recent emerging evidence suggest adding mycophenolate mofetil to patients with lupus nephritis is superior to IV cyclophosphamide. 11 Early diagnosis of SLE is the key to optimum management and better outcome of the patient, because juvenile SLE has more aggressive disease course, greater morbidity and mortality than adult onset disease. 10 Diffuse lymphadenopathy as the presenting symptom of SLE is not common today, however it should not be forgotten as in our case to avoid delay in making the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, it may be easier to overlook hyperuricemia in female kidney transplant recipients. In addition, many patients with lupus nephritis tend to be women and these patients are prescribed MMF and corticosteroids for their condition [23]. Patients with these conditions greatly resemble kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%